Progress of Transposon Vector System for Production of Recombinant Therapeutic Proteins in Mammalian Cells - Wei, Mian; Mi, Chun-Liu; Jing, Chang-Qin; Wang, Tian-Yun (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years, mammalian cells have become the primary host cells for the production of recombinant therapeutic proteins (RTPs). Despite that the expression of RTPs in mammalian cells can be improved by directly optimizing or engineering the expression vectors, it is still influenced by the low stability and efficiency of gene integration. Transposons are mobile genetic elements that can be inserted and cleaved within the genome and can change their inserting position. The transposon vector system can be applied to establish a stable pool of cells with high efficiency in RTPs production through facilitating the integration of genes of interest (GOI) into transcriptionally active sites under screening pressure. Here, the structure and optimization of transposon vector system and its application in expressing RTPs at high level in mammalian cells are reviewed.